О синтезе алмаза - Кулакова, И.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Features of chemical diamond synthesis from little carbon containing molecules in soft P,Tconditions are considered. Chemical diamond synthesis model in nature is suggested. It is produced proofs of diamond growth as metacrystal in solid kimberlite. Physico-chemical criterion for estimation of diamonds abundance in kimberlite is created.